CONTEMPORARY METHODS FOR SOIL AND WATER PROTECTION FROM THE IMPACT OF RAILWAY TRAFFIC - Dimitrijević Jelena; Bonić Zoran; Milićević Dragan; Zafirovski Zlatko (University of Niš, Serbia, 2023)
One of the basic assignments of modern society is preserving the quality of freshwater resources, especially drinking water. Line facilities potentially pose a higher risk to the environment due to the large length of the extension and the diversity of the environment they may affect. Storm water drained from railway could pollute the surrounding land besides railway track. Based on the data from available research, it has been determined that heavy metals (iron, copper, zinc, manganese and chromium), polycyclic aromatic hydrocarbons (PAHs) and herbicides stand out in significant quantities from substances hazardous to the environment. This paper proposes the solutions using some self-sustainable techniques, based on the analysis railway drainage needs. The proposals that have been made refer to the open-air railway and railway station.
Keywords: railway drainage, railway station drainage, self-sustainable drainage techniques